β-glucosidase: An overview on immobilization and some aspects of structure, function, applications and cost - Mól, Paula Chequer Gouveia [UNESP]; Júnior, José Carlos Quilles; Veríssimo, Lizzy Ayra Alcântara; Boscolo, Mauricio [UNESP]; Gomes, Eleni [UNESP]; Minim, Luis Antonio; Da Silva, Roberto [UNESP] (Elsevier, 2023)
β-glucosidases constitute a heterogeneous group of well-characterized and biologically important hydrolytic enzymes which act on different substrates. They have been widely utilized in biotechnology. Nowadays, immobilized β-glucosidase has become one of the most important biocatalytic systems used for many industrial purposes, especially in the biofuel, food, pharmaceutical and beverage industries. Immobilized β-glucosidase has the advantages of usually being chemically and thermally more stable, easily separated from the product, possible to reuse and can replace chemical catalysts in some industrial applications. From both a scientific and application point of view, interest in developing new support materials and new protocols for β-glucosidase immobilization has grown. This review focused on originality and novelty on how an immobilization system for β-glucosidases should be and what is missing for really efficient applications. For that, the main methods used for the immobilization of β-glucosidase and the description of the different support materials, with emphasis on their advantages and disadvantages; the main physical-chemical characteristics of immobilized enzymes; the applications of the pure or mixed immobilized enzyme; and a discussion on the β-glucosidase market and cost are presented. Finally, the overall conclusion is given along with a mention of perspectives and future directions.
Keywords: Cost; Immobilization; Support materials; β-glucosidase; β-glucosidases applications